Modification Of Hospital Formula Based On Yellow Pumpkin Flour (Curcubita Moschata) And Egg White Flour For Patients With Diabetic Nephropathy - Najma Zahara Putri Hilda; Nur Rahman; Fifi Luthfiyah (Jurnal Gizi Prima (Prime Nutrition Journal), 2024)
Background: Diabetes mellitus is a metabolic disorder characterized by increased blood glucose levels, which can cause complications, one of which is diabetic nephropathy. One of the preventive therapies that can be carried out is administering an enteral formula high in protein and fiber. It is possible that yellow pumpkin and egg whites can help reduce the risk of developing diabetes.Research Purpose: This research aims to develop hospital enteral formulas, determine their viscosity, analyze their nutritional content, and determine their organoleptic quality.Research Methods: This research uses a quasi-experimental method, with the research design used as a static group comparison. Viscosity testing uses a viscometer, water, ash, protein, and fat. Carbohydrate content testing uses proximate analysis, and food fiber content testing uses the enzymatic method. Organoleptic testing uses a hedonic scale, and the panelists are semi-trained.Research Result: The results showed differences in cholesterol levels before and after the study (p=0.00). The treatment group had a reduced cholesterol level of 57.8 mg/dL, and the control group had a reduced cholesterol level of 34.3 mg/dL. However, the benefits of green bean juice with cinnamon powder in lowering cholesterol levels were not statistically significant (p=0.074). Conclusion: A modified formula based on pumpkin flour and egg white flour has the potential to be an alternative food for people living with diabetes.